Mexican migration to the United States: Underlying economic factors and possible scenarios for future flows - Daniel Chiquiar; Alejandrina Salcedo (Banco de México, 2013)
In this paper we examine some economic factors that have influenced migration flows from Mexico to the United States since 1990 for the purpose of constructing scenarios on how such flows could evolve in the near term. In particular, we link the behavior of migration to changes in sectoral growth in the US, as well as to a heterogeneous participation of Mexican workers in employment by sector. To forecast future migration flows, we propose and estimate a model of demand for Mexican labor by US sector and use it to construct possible scenarios for migration flows. While the estimation is subject to a high degree of uncertainty, the main conclusion is that net migration flows of Mexicans to the United States over the coming years are likely to increase compared to what was observed during the recent global economic crisis, but that such flows are very unlikely to reach the levels registered during the 1990s.
Keywords: O15; J23; J61; J82; 330; migration flows; labor demand; US sectoral growth